Temporomandibular joint dysfunction and its association with the stress reactivity index in a hospital of Valencia, Venezuela - Agurto-Castro, Jorge Augusto (2022)
Introduction: Lifestyles imposed by constant transformations and increasing demands have triggered a high level of stress, this phenomenon has been related to several pathologies including temporomandibular joint dysfunction. Methods: A descriptive cross-sectional study was carried out, considering a sample of 100 patients who attended a consultation of Buccomaxillofacial Surgery at the Dr. Enrique Tejera Hospital in Valencia, Venezuela; each participant completed the stress reactivity index questionnaire (IRE-32). The data collected were analyzed by descriptive and inferential statistics. Results: Evidence of association was obtained between the variables of temporomandibular joint dysfunction and the stress reactivity index according to age and sex. Conclusions: Stress and TMJ disorders are undoubtedly linked and therefore it is important the timely identification and control of stressful conditions for each patient according to their reactivity to them.